THE EFFICACY OF EXERCISE AND CALCIUM TREATMENT IN POSTMENOPAUSAL OSTEOPOROSIS - Esma Ceceli,; Selda Kısaoğlu,; Meryem Saraçoğlu,; Seher Kocaoğlu,; Z. Rezan Yorgancıoğlu, (Archives of Rheumatology, 2001)
This study was planned to examine whether there is a role of exercise in improving bone mineral density (BMD) in female with postmenopausal osteoporosis. 14 female with postmenopausal osteoporosis participated in the study. L2-4 BMD of the subjects was measured by DEXA. The subjects performed exercise three days a week for six months. Exercise sessions consisted of 15-20 minutes of warm-up, 25-30 minutes of abdominal and back muscle strengthening exercises and 10 minutes of cool down periods. In addition to exercise 1000 mg of calcium was given to all subjects. At the end of six months control BMD was measured. Initial and control BMD values were compared by Wilcoxon test. The BMD of L2-4 at the beginning was between 0,728 gr/cm2 and 0,982 gr/cm2 and the BMD values at the end of six months were between 0,769 gr/cm2 and 1,029 gr/cm2. The BMD values were increased in all of the patients and the difference was statistically significant (p=0,001). The results of this study indicate that regular exercise and calcium intake had a positive effect on BMD.